ANALISIS PRAKTEK SHARENTING SEBAGAI UPAYA MEMENUHI KEBUTUHAN SELF ESTEEM PADA IBU MUDA - Maulidiyah, Ummi Masrufah; arumsari, andini dwi (MOTORIC, 2024)
The research was conducted to understand how the need for appreciation or self-esteem is a factor for young mothers in practicing sharenting and to find out how the phenomenon of sharenting itself generally occurs in various countries in the world. Sharenting itself is a combination of two words, "parenting" and "sharing". Included in the practice of sharenting include sharing photos, videos, personal stories or other novelties related to children's activities such as eating, bathing, and play (Healthcare Basel, 2023). A person must fulfill these needs from the most basic, namely physiological needs, continuing the need for security, then the need for belonging and love, then the need for appreciation or self-esteem and the highest is the need for self-actualization. The research method used in this journal article is descriptive research. Descriptive research aims to systematically and accurately describe facts and characteristics about the population or about a particular field. The results of the study contain research data that is relevant to the goals of the final project and knows the phenomenon of sharenting in various countries. The high number of internet users around the world makes it massive for someone to share an activity or something they want to share on social media, of the 173.59 million Indonesian population are Instagram users with an achievement of 84.80% in 2023 and are more dominated by Gen Z at 27.9% and the millennial generation at 25.87% (Pangudi & Yusriana, 2023) and information distribution through Facebook reaches 5.02 million status updates per day and Twitter activity reaches 7.35 million tweets or retweets per day. Keywords: Sharenting, self esteem, young mother